SPEECH REHABILITATION OF PATIENTS WITH ORAL CAVITY AND OROPHARYNGEAL CANCERS AFTER RECONSTRUCTIVE SURGERY - E. A. Krasavina; E. L. Choynzonov; D. E. Kulbakin; L. N. Balatskaya; K. A. Zangieva (Сибирский онкологический журнал, 2020)
Oral cavity and oropharyngeal cancers usually require extensive surgeries accompanied by damages to anatomical structures and impaired speech function. The use of reconstructive-plastic techniques to replace defects after surgical resection allows the creation of a favorable functional basis for speech restoration.The purpose of the study was to compare the effectiveness and terms of speech restoration in patients with oral cavity and oropharyngeal cancers after surgical treatment using various reconstructive surgery techniques to restore postoperative defects.Material and Methods. Speech rehabilitation results were analyzed in 56 patients with stage II–IV oral cavity and oropharyngeal cancers. The age of the patients ranged from 26 to 70 years. The patients underwent either hemiglossectomy or glossectomy followed by reconstructive surgery. Postoperative speech rehabilitation was performed according to the technique developed in the Department of Head and Neck Tumors of the Cancer Research Institute. Speech function was assessed before starting treatment, at the beginning of treatment and after completion of speech rehabilitation.Results. After surgery, all patients demonstrated impaired speech function, ranging from distorted pronunciation to the complete absence of verbal communication for 5 (71.4%) and 4 (80%) patients from Ib and IIb respectively. Speech rehabilitation started 16 to 32 days after surgery. Restoration of the activity and coordination of the articulatory apparatus muscles, speech exhalation and reconstructed tongue was followed by a sound pronunciation. Postoperative speech rehabilitation allowed improvement of speech function in 100 % of cases (56 patients). A complete speech restoration was achieved for 7 patients (12.5%). The majority of these patients were from the group with hemiglossectomy. In the group of patients with glossectomy, the amplitude and coordination of movements, which could be achieved by performing articulation exercises for the reconstructed tongue, depended on the size of the remaining part of their own tissues.Conclusion. Good values of all studied parameters were observed in patients, who underwent hemiglossectomy followed by reconstruction with a free revascularized flap. No statistically significant differences between the studied parameters were found in patients, who underwent glossectomy. Speech restoration parameters were significantly better in the group of patients with hemiglossectomy and reconstruction with a free revascularized flap than in the group of patients with glossectomy).